2021
DOI: 10.46328/ijtes.261
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Utilization of Computer-Based Technology in Science Instruction

Abstract: With the onset of Education 4.0 and the VUCAD2 world, the use of technology in instruction has been fully maximized. This study aimed to determine the teachers’ utilization of computer-based technology in science instruction. The study used descriptive survey research using the Computer-Based Technology Inventory Survey Questionnaire (CBTI-SQ). A total of 41 science teachers in two state-owned secondary schools in Zambales, Philippines served as respondents in the study. Based on the findings, the computer-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…The findings of Gombe et al (2016) also showed that lecturers with Ph.D qualification had a slightly higher mean rating, followed by those with Masters' degree, while those with Bachelors' degrees had the least mean rating. However, the result agrees with (Olafare et al, 2018;Paje, Rogayan, & Dantic, 2021) who found a significant difference in knowledge of use of ICT by lecturers based on their qualifications.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of Gombe et al (2016) also showed that lecturers with Ph.D qualification had a slightly higher mean rating, followed by those with Masters' degree, while those with Bachelors' degrees had the least mean rating. However, the result agrees with (Olafare et al, 2018;Paje, Rogayan, & Dantic, 2021) who found a significant difference in knowledge of use of ICT by lecturers based on their qualifications.…”
Section: Discussionsupporting
confidence: 90%
“…However, it disagrees with (Olelewe & Okwor, 2017;Nwachukwu & Asom, 2015) whose research found that most teachers cannot use ICT facilities in teaching. The result of this study is also at variance with the work of Ogunshola,( 2019) and Paje, Rogayan, & Dantic, (2021) who agreed that there was a significant relationship between teachers' digital technology resources utilization, and teaching and learning in schools. This led the researcher to conclude that the use of computer technology resources facilitated teaching and learning in private senior secondary schools.…”
Section: Discussioncontrasting
confidence: 67%
“…Teachers are challenged to improve the students' digital literacy, which is one of the core skills they need to have as they hurdle the challenges of the current educational landscape and the fourth industrial revolution or FIRe (Baterna et al, 2020). Further, it is a must for 21 st -century teachers to have computer skills to cope up with the needs of 21 st -century learners (Paje et al, 2021). With the utilization of CAI, this challenge can be surmounted.…”
Section: Relationship Between Motivation and Academic Performancementioning
confidence: 99%
“…However, when we look at the factors affecting the computer-assisted instruction process, it is seen that it includes various variables such as lesson outcomes, student motivation, innovations, interaction, individual learning differences, the type, scope and quality of the courseware, the teacher's perception, attitude, expectation and changing role in computer-assisted education, the integration of the curriculum with the education program, and the way computer-assisted education is carried out in the school (Cotton, 2008;Paje, Rogayan & Dantic, 2021Şahin & Yıldırım 1999Warschauer & Healey 1998). On the other hand, Online and Blended learning has proved to be a vital instrument for increasing learners' motivation and satisfaction (Aslan, 2016).…”
Section: Introductionmentioning
confidence: 99%